Top Management Support Functions in Higher Education Management Accounting Information Systems - Lesi Hertati; Nazarudin Nazarudin; Irlan Fery (Ilomata International Journal of Tax and Accounting, 2020)
The function of the management accounting information system is very important in universities, as it provides input to leaders for accurate decision making. Higher education leaders must listen more and provide good work management and require an accounting system in order to survive amid the heavy workload of lecturers that are not balanced with balanced wages. Accounting information systems can help universities expand their reach to remote locations, acquire new forms and workflows, and possibly change teaching patterns virtually. The management accounting information system is a collection (integration) of sub-systems / components, both physical and non-physical, which are interconnected and harmoniously cooperate with each other to process transaction data related to financial matters into financial information. The purpose of this study was to determine the effect of top management support on the function of the accounting system. The unit of analysis in this research is the related sub-unit within the management of higher education institutions in South Sumatra-Indonesia. The results showed that top management support greatly influenced the function of the management accounting information system. The results of the study found that the life cycle of accounting information system development supports top management which includes planning, design and implementation (top management support is conceptualized as the involvement and participation of top-level management of the organization in information technology / accounting information system activities on lecturer work reports, lecturer salaries and managers. College.